Recent progress in the design, synthesis and applications of chiral metal-organic frameworks - Altaf, Amna; Hassan, Sadia; Pejcic, Bobby; Baig, Nadeem; Hussain, Zakir; Sohail, Manzar (Frontiers in Chemistry, 2022)
Chiral Metal-Organic Frameworks (MOFs) are unique crystalline and porous materials composed of organic linkers and metal ions. Chiral MOFs surpass traditional organic and inorganic porous materials because of their tunable shape, size, functional diversity, and selectivity. Specific applications of chiral MOFs can be exploited by introducing desired functional groups. Chiral MOFs have recognition abilities, making them unique for chiral compound synthesis and separation. Synthetic strategies play an essential role in getting selected properties in MOFs. Chiral MOFs find potential applications in adsorption, asymmetric catalysis, luminescence, degradation, and enantioselective separation. The MOFs' porosity, stability, and reusability make them attractive materials for these applications. Herein, the advances in the synthetic methods of chiral MOFs and their various applications have been discussed.